2022
DOI: 10.3390/antiox11081590
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Stress in Atopic Dermatitis and Chronic Urticaria

Abstract: Atopic dermatitis (AD) and chronic urticaria (CU) are common skin diseases with an increasing prevalence and pathogenesis that are not fully understood. Emerging evidence suggests that oxidative stress plays a role in AD and CU. The aim of the single-center cross-sectional study was to compare markers of oxidative stress in 21 patients with AD, and 19 CU patients. The products of protein oxidation, total antioxidant capacity (TAC), and markers of lipid peroxidation were estimated in the serum. AD patients had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 66 publications
2
17
0
Order By: Relevance
“…28 Association between two diseases can be explained by immunological dysregulation, shared genetic factors, and oxidative stress. 29,30 Here, we found that atopic dermatitis had a stronger association with chronic urticaria and psoriasis than with asthma or allergic rhinitis, which is consistent with previous findings. 31 Although the association between atopic dermatitis and allergic comorbidities is well recognized, its association with autoimmune diseases is less clear and should be considered in the management and follow-up of children with atopic dermatitis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…28 Association between two diseases can be explained by immunological dysregulation, shared genetic factors, and oxidative stress. 29,30 Here, we found that atopic dermatitis had a stronger association with chronic urticaria and psoriasis than with asthma or allergic rhinitis, which is consistent with previous findings. 31 Although the association between atopic dermatitis and allergic comorbidities is well recognized, its association with autoimmune diseases is less clear and should be considered in the management and follow-up of children with atopic dermatitis.…”
Section: Discussionsupporting
confidence: 92%
“…A large, nationwide cross‐sectional study of adolescents showed that atopic dermatitis was associated with chronic urticaria (odds ratio: 2.35, 95% CI: 2.03–2.72) 28 . Association between two diseases can be explained by immunological dysregulation, shared genetic factors, and oxidative stress 29,30 . Here, we found that atopic dermatitis had a stronger association with chronic urticaria and psoriasis than with asthma or allergic rhinitis, which is consistent with previous findings 31 .…”
Section: Discussionsupporting
confidence: 91%
“…LPO products cause disruption of not only lipid bonds in biomembranes and their protein component -due to binding with amine groups, which leads to disruption of protein-lipid interaction. Free radical oxidation of lipids causes changes in fiber elasticity and initiates fibroplastic processes and collagen aging [2,15].…”
Section: Resultsmentioning
confidence: 99%
“…Encapsulation of linalool improves its stability [48,57] and consequently increases its antioxidant activity since the terpene itself has radical-scavenging ability [58]. The higher radical-scavenging ability is important to ensure a more effective skin treatment as oxidative stress can worse dermatological diseases [59,60].…”
Section: Citrus Terpenes Loaded Into Nanocarriersmentioning
confidence: 99%